Development of low-cost real-time data acquisition system for process automation and control - Haizad, M. (Institute of Electrical and Electronics Engineers Inc., 2017)
The use of data acquisition system (DAQ) is important in process industry as it enables analog signal from physical system to be converted into a digital signal for processing by computer and vice versa. However, many of the DAQs available in the market today are complex and expensive. This paper presents the development of a simple, low-cost and open source microcontroller-based DAQ system for process automation and control. The proposed DAQ system is built around Arduino Mega 2560 microcontroller. The test experimental results of the developed DAQ system proved its suitability for application in process monitoring and control applications. © 2016 IEEE.